2015
DOI: 10.1002/hipo.22428
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a sustained neurogenic zone at the dorsal surface of the adult mouse hippocampus and its regulation by the chemokine SDF‐1

Abstract: We identified a previously unknown neurogenic region at the dorsal surface of the hippocampus; (the “subhippocampal zone,” SHZ) in the adult brain. Using a reporter mouse in which SHZ cells and their progeny could be traced through the expression of EGFP under the control of the CXCR4 chemokine receptor promoter we observed the presence of a pool of EGFP expressing cells migrating in direction of the dentate gyrus (DG), which is maintained throughout adulthood. This population appeared to originate from the SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…In rodents, the hippocampal fissure, equivalent to the sulcus in humans, has also been identified as a niche and further potential source of progenitor cells in adult animals . A further migratory stream has been described in mice extending from the hippocampal fimbra to dentate, composed of radial-glial like cells, which persists into adulthood (Belmadani et al, 2015). Recent studies of human hippocampal development also identify the fimbria as a further source of progenitor cells for the dentate gyrus (Cipriani et al, 2015).…”
Section: Nec In Developmental and Mature Nichesmentioning
confidence: 99%
“…In rodents, the hippocampal fissure, equivalent to the sulcus in humans, has also been identified as a niche and further potential source of progenitor cells in adult animals . A further migratory stream has been described in mice extending from the hippocampal fimbra to dentate, composed of radial-glial like cells, which persists into adulthood (Belmadani et al, 2015). Recent studies of human hippocampal development also identify the fimbria as a further source of progenitor cells for the dentate gyrus (Cipriani et al, 2015).…”
Section: Nec In Developmental and Mature Nichesmentioning
confidence: 99%
“…Afterwards, an explanation for mismigration was proposed: It was shown that HIPP cells secrete reelin, which normally prevents cells from migrating to the source of reelin, whereas after HIPP cell death, hilar reelin was reduced. 53 Many years later, it was also shown that the GCs might emerge from the septohippocampal zone, 54 or the hilus itself, because progenitors and young GCs appear to be present in the hilus normally. 55 When recordings were made of the hilar "ectopic" granule cells (EGCs), it was shown that they have axons that innervate normal GCs and CA3 pyramidal cells, possibly mediating the synchronization needed for a seizure focus.…”
Section: Adult Neurogenesis In Tlementioning
confidence: 99%
“…SDF-1 was initially defined as a regulatory signaling protein required by peripheral hematopoietic stem cells (HSCs). However, SDF-1 also plays an important role in maintaining embryonic and adult NPCs (Addington et al, 2014;Belmadani et al, 2015;Nagasawa, 2014). Additionally, SDF-1 is predicted to contribute to the recruitment of NPCs to damaged regions to enhance recovery (Li et al, 2012;Merino et al, 2015).…”
Section: Introductionmentioning
confidence: 99%